Ultrasound-irradiated synthesis of 3-mercaptopropyl trimethoxysilane-modified hydroxyapatite derived from fish-scale residues followed by ultrasound-assisted organic dyes removal - Phitchan Sricharoen; Supalak Kongsri; Chunyapuk Kukusamude; Yonrapach Areerob; Prawit Nuengmatcha; Saksit Chanthai; Nunticha Limchoowong (My University, 2021)
Abstract We report a novel method for the synthesis of 3-mercaptopropyl trimethoxysilane-modified hydroxyapatite (FHAP-SH) derived from fish-scale residues by using ultrasound irradiation. Scanning electron microscopy, transmission electron microscopy, energy-dispersive spectroscopy, X-ray diffraction, and Fourier transform infrared spectroscopy were used for the FHAP-SH characterization. Then, the organic dye adsorption on the FHAP-SH was monitored through an ultrasound process. After the dye removal optimization, significant improvements were observed in the maximum adsorption capacities for Congo Red (CR, 500 mg g −1 ), Coomassie Brilliant Blue G 250 (CB, 235 mg g −1 ), and Malachite Green (MG, 625 mg g −1 ). The adsorption behaviors of these dyes were fitted by using the Langmuir isotherm model with a high coefficient of determination values ranging from 0.9985 to 0.9969. The adsorption of the three dyes onto FHAP-SH was an endothermic process based on the adsorption thermodynamics model, while the adsorption kinetics analysis of the dyes presented a good alignment with the pseudo-second-order kinetics. The FHAP-SH exhibits a remarkably high adsorption capacity, is inexpensive, and fulfills the ecofriendly requirements of dye wastewater treatment, especially in the textile industry.
Keywords: Malachite green; Langmuir adsorption model; Congo red; Endothermic process; Adsorption and biosorption for pollutant removal